Influence of heat flow direction on solder ball interfacial layer - Otáhal, Alexandr; Szendiuch, Ivan (My University, 2018)
This paper deals with the research of an intermetallic layer of SAC305 solder balls soldered from three directions of the heat flow in the ball-attach process for BGA package. From the point of view of the heat flow direction, the samples were soldered by infrared heating. The heat sources were placed on the top, bottom and both lateral sides of the BGA package. After the solder balls-attach process, a metallographic cross-section was performed, followed by selective etching to visualize the relief of the intermetallic layer. Images of the interfacial between the solder and solder pad were taken from the created samples, followed by measurement of the average thickness and root mean square roughness of the intermetallic layer. The results showed changes in the intermetallic layer. The largest thickness of the intermetallic layer was observed on samples soldered from the top and both sides. Soldering with the bottom infrared heater resulted to the smallest thickness of the intermetallic layer. The same trend was in the roughness of the IMC layer. The greatest roughness was found for samples soldered by the top and both side heaters. The top soldered samples exhibit the smallest roughness.

This paper deals with the research of an intermetallic layer of SAC305 solder balls soldered from three directions of the heat flow in the ball-attach process for BGA package. From the point of view of the heat flow direction, the samples were soldered by infrared heating. The heat sources were placed on the top, bottom and both lateral sides of the BGA package. After the solder balls-attach process, a metallographic cross-section was performed, followed by selective etching to visualize the relief of the intermetallic layer. Images of the interfacial between the solder and solder pad were taken from the created samples, followed by measurement of the average thickness and root mean square roughness of the intermetallic layer. The results showed changes in the intermetallic layer. The largest thickness of the intermetallic layer was observed on samples soldered from the top and both sides. Soldering with the bottom infrared heater resulted to the smallest thickness of the intermetallic layer. The same trend was in the roughness of the IMC layer. The greatest roughness was found for samples soldered by the top and both side heaters. The top soldered samples exhibit the smallest roughness.
Influence of heat flow direction on solder ball interfacial layer
Keywords: BGA package; reflow soldering; infrared heater; heat flow direction; intermetallic interfacial layer; BGA package; reflow soldering; infrared heater; heat flow direction; intermetallic interfacial layer